Structural binding perspectives of a major tobacco alkaloid, nicotine, and its metabolite cotinine with sex‐steroid nuclear receptors. Issue 10 (28th April 2020) - Rehan, Mohd; Ahmad, Ejaz; Beg, Mohd A.
Abstract: Globally, more than a billion people smoke tobacco making it one of the biggest public health problems and a leading risk factor for global deaths. Nicotine, the main alkaloid in tobacco, has been shown to be associated with fertility problems in men and women. The adverse effects of tobacco/nicotine on reproduction have been attributed to deleterious effects on gametes, steroidogenic imbalance, and competitive inhibition of steroid receptors. The present study reports the sex‐steroid receptor disrupting potential of nicotine and its major metabolite cotinine against the estrogen receptor‐α (ERα), ERβ, androgen receptor (AR), and progesterone receptor (PR). Both ligands bound in the ligand‐binding pockets of ERα, ERβ, AR and PR and formed important hydrophobic interactions with different amino‐acid residues of receptors. Most of the residues of ERα, ERβ, AR and PR interacting with nicotine and cotinine were common with those of native/bound ligands of the receptors. Interacting amino acids most important for binding of nicotine and cotinine with each receptor were identified by loss in accessible surface area. Amino acids Leucine‐346, Leucine‐384 and Phenylalanine‐404 for ERα; Methionine‐336, Phenylalanine‐356 and Leucine‐298 for ERβ; and Leucine‐704 and Leucine‐718, respectively for AR and PR, were the most important residues for binding with nicotine and cotinine. Among the four receptors, based on the number of interactions, nicotine and cotinine had greater potential to interfere in the signaling of ERβ. In conclusion, the results suggested that nicotine and cotinine bind and interact with sex‐steroid nuclear receptors and have potential to interfere in the steroid hormone signaling resulting in reproductive dysfunction. Abstract : Nicotine, the main alkaloid in tobacco, is associated with fertility problems in men and women. Structural‐binding interactions of nicotine and its metabolite cotinine with estrogen receptor‐α (ERα), ERβ, androgen receptor (AR) and progesterone receptor (PR) were characterized. Important amino acids for binding of nicotine and cotinine were Leucine‐346, Leucine‐384, Phenylalanine‐404 for ERα; Methionine‐336, Phenylalanine‐356 for ERβ; and Leucine‐704 and Leucine‐718, respectively, for AR and PR. Concluding, nicotine and cotinine have potential to interfere in steroid hormone signaling and cause reproductive dysfunction.